Charmed forces - Morgan, Melissa J. (New York : Grosset & Dunlap, 2008)
Another summer at Camp Lakeview begins with Alyssa finding an amethyst that seems to give her psychic powers, and the girls of bunk 6B are split over whether or not to believe in her abilities which include such predictions as snow in July.
Keywords: Camps -- Juvenile fiction; Psychic ability -- Juvenile fiction; Precious stones -- Juvenile fiction; Friendship -- Juvenile fiction; Pennsylvania -- Juvenile fiction